2000
DOI: 10.1044/1058-0360.0904.300
|View full text |Cite
|
Sign up to set email alerts
|

A Coding System for Describing Conversational Breakdowns in Preschool Children

Abstract: Analysis of children’s breakdowns offers a rich data source, potentially revealing patterns of weakness in children’s communication ability. The purpose of the present study was to present a fine-grained instrument, the Breakdown Coding System (BCS; Yont, 1998), for measuring conversational breakdowns in preschoolers. The BCS was applied to language samples collected from five typically developing children (ages 3;11–4;2 years) during naturalistic interactions with familiar caregivers. Results indicated that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…In fact, this kind of adjustment has been observed in shared book‐reading interactions between mothers and toddlers or young preschoolers with TD language (De Temple 2001). Yont et al (2000) showed that linguistic errors (phonological, lexical, syntactic errors) and inappropriate content in the answers of children with SLI, as well as their frequent lack of responsiveness, are evident sources of conversational breakdown during free‐play interaction. Consistent with this idea, Vander Woude and Barton (2001, 2003) suggested that increased parental talking during shared reading may benefit the child in case the conversational strategies used by the parents are aimed at positioning the child as a communicatively competent participant during shared reading conversation.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, this kind of adjustment has been observed in shared book‐reading interactions between mothers and toddlers or young preschoolers with TD language (De Temple 2001). Yont et al (2000) showed that linguistic errors (phonological, lexical, syntactic errors) and inappropriate content in the answers of children with SLI, as well as their frequent lack of responsiveness, are evident sources of conversational breakdown during free‐play interaction. Consistent with this idea, Vander Woude and Barton (2001, 2003) suggested that increased parental talking during shared reading may benefit the child in case the conversational strategies used by the parents are aimed at positioning the child as a communicatively competent participant during shared reading conversation.…”
Section: Introductionmentioning
confidence: 99%
“…A system for coding breakdowns in conversations (Breakdown Coding System) with young children, described by Yont, Howard, and Miccio (2000) holds considerable potential for a focused practical assessment of repair strategies. Adult clarification requests are divided into a) further information required, b) more sophisticated information required, c) lack of comprehension, d) unintelligibility, e) to fill in a turn.…”
mentioning
confidence: 99%
“…Though universally accepted definitions of behaviors associated with communication breakdowns do not exist, we drew from well-established literature to formulate the following definitions. A communication breakdown consisted of a child's problematic utterance and a mother's RQCL (Yont et al 2000). A mother's RQCL served to signal a misunderstanding and asked the child to repair the utterance.…”
Section: Methodsmentioning
confidence: 99%
“…When a listener indicates that he or she does not understand the speaker's communication turn during conversation and requests clarification, the speaker must provide a repair in order for the conversation to continue successfully. A variety of communication difficulties stemming from the speaker, including reduced volume; phonological, lexical, and pragmatic errors; and unclear use of gestures, can lead to breakdowns in conversation (Yont et al 2000). As noted by Brady et al (2005), the ability to repair breakdowns is essential for children with disabilities, who often have difficulty communicating and depend on successful repairs to reach their communication goals.…”
mentioning
confidence: 99%